Widened mediastinum on chest radiography as a prompt for further imaging in suspected blunt traumatic aortic injury: 3-year experience at a major trauma centre - Dzamatira, Davison (Division of Radiology, 2023)
Background: Trauma clinicians utilise the presence of a widened mediastinum on a chest radiograph (CXR) as the commonest indication for chest computed tomography (CT) in cases of suspected blunt traumatic aortic injury (BTAI). Evaluating the practical implementation and accuracy of this tool could improve the degree of interdepartmental agreement on its correct application. Objectives: To establish the proportion of requests by requesting clinicians citing a widened mediastinum on radiography that met the established criteria for true widening. A secondary objective was to determine the percentage of confirmed blunt traumatic aortic injury and other serious injuries in our study population at Groote Schuur Hospital. Methods: A retrospective descriptive study was conducted measuring the mediastinal widths on chest radiographs of all patients suspected of BTAI that had chest CT at Groote Schuur Hospital over a three-year period from 01 January 2017 to 31 December 2019 to establish the accuracy of this sign as a predictor of aortic injury. Results: In total, 223 patients had chest CT performed to exclude BTAI. 85.7 % of clinicians' requests for chest CT met the current criteria for a widened mediastinum on supine CXR or LODOX. Aortic injury was confirmed in 4 patients (2%). Other serious injuries included thoracic vertebral fractures of at least one vertebral body which was present in 19 patients (8.5%), and 1 patient (0.45%) had a diaphragmatic rupture. None of the patients had a cardiac injury. 200 out of 223 patients (89.7%) had neither an aortic injury nor any of the serious injuries described above. Conclusion: The study demonstrated a high level of accuracy by clinicians in diagnosing widening of the mediastinum on LODOX and CXR. These findings can be used to further improve interdepartmental agreement in the evaluation and management of patients with suspected BTAI.